MUSICAL AND CREATIVE ENVIRONMENT AS A CONDITION FOR THE PROFESSIONAL ACTIVITY OF A TEACHER - Makhfuza Makhamadjonovna Khalilova (Journal Park Publishing, 2023)
In the study, an attempt was made to study the features of the musical and creative environment in the professional activities of a teacher. Goals and objectives of this work: consider the historical and theoretical aspects and prerequisites of the musical and creative environment (periods of formation of musical education); identify the key methodological systems of musical education and upbringing (components) as prior experience in music pedagogy; identify the features of the project method in the musical and creative environment, as a productive training for the future professional activity of a teacher.
Keywords: musical and creative environment, project method, design, self-designing, professional activity, personality quality, reflection, emotional responsiveness, creativity, productivity.